2020
DOI: 10.3390/biomedicines8060137
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Disrupting Chemicals and Insulin Resistance in Children

Abstract: The purpose of this article is to review the evidence linking background exposure to endocrine-disrupting chemicals (EDCs) with insulin resistance in children. Although evidence in children is scarce since very few prospective studies exist even in adults, evidence that EDCs might be involved in the development of insulin resistance and related diseases such as obesity and diabetes is accumulating. We reviewed the literature on both cross-sectional and prospective studies in humans and experimental studies. Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 121 publications
(153 reference statements)
1
12
0
1
Order By: Relevance
“…There is a growing body of evidence that EDCs target several pathophysiologic features of GDM, such as weight gain, insulin resistance, and pancreatic -cell function [ 84 , 107 , 108 ]. EDCs influence the activity of peroxisome proliferator-activated receptors, which are crucially involved in glucose metabolism and energy homeostasis.…”
Section: General Aspects Of Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…There is a growing body of evidence that EDCs target several pathophysiologic features of GDM, such as weight gain, insulin resistance, and pancreatic -cell function [ 84 , 107 , 108 ]. EDCs influence the activity of peroxisome proliferator-activated receptors, which are crucially involved in glucose metabolism and energy homeostasis.…”
Section: General Aspects Of Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…Studies investigating EDCs’ impact on fetal–placental epigenetics in human pregnancy are sparse because of the ethical issues associated to the collection of samples during the first trimester of pregnancy. EDCs induce genome alterations in pregnancy or early life and enchain in a decreased expression of pancreatic/duodenal homeobox 1 transcription factor gene (PDX-1) associated with an increase in T2D (review in [ 157 ]), suggesting that in utero exposure to impaired nutrition is a risk for obesity and diabetes progression in adulthood. EDCs confine the stock of essential metabolic substrates to the fetus and cause intrauterine growth retardation, presenting as fetal starvation and the metabolic basis that triggers diabetes progression in PDX-1.…”
Section: Hypothesis Of Different Mechanisms Leading To MDmentioning
confidence: 99%
“…Furthermore, data obtained in human and different cell lines show that BPA interferes with thyroid hormones synthesis, secretion, and signaling. Due to its anti-androgenic action, BPA works as an agonist on estrogen receptors and antagonist on androgen receptors [ 35 ]. Recently, it has been shown that BPA interferes with spermatogenesis and impairs male reproductive function.…”
Section: Introductionmentioning
confidence: 99%